2023
DOI: 10.3389/fmicb.2023.1084025
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of bacteriophages infecting Xanthomonas oryzae pv. oryzae and genomic characterization of novel phage vB_XooS_NR08 for biocontrol of bacterial leaf blight of rice

Abstract: Bacterial leaf blight (BLB) disease of rice caused by Xanthomonas oryzae pv. oryzae (Xoo) is one of the most destructive diseases worldwide in rice-growing regions. The Ineffectiveness of chemicals in disease management has increased the interest in phage therapy. In this study, we isolated 19 bacteriophages, infecting Xoo, from a rice field, which belonged to phage families Siphoviridae, Myoviridae, and Podoviridae on the basis of electron microscopy. Among 19 phages, Phage vB_XooS_NR08, a member of the Sipho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Reviewed research on phage-based biocontrol of plant pathogens is targeting the most common and destructive plant pathogens and includes some Xcc trials [ 22 ]. A number of studies have shown that the use of phages to control bacterial plant diseases is a promising option, because they are cheap to produce, self-destructible, and safe for the host organism and the biosphere, since they are a natural part of it [ 68 , 69 ]. An undeniable advantage of phages in comparison with other agents for the control of bacterial diseases is the possibility of their use to control synthetic biocide-resistant forms of bacteria [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Reviewed research on phage-based biocontrol of plant pathogens is targeting the most common and destructive plant pathogens and includes some Xcc trials [ 22 ]. A number of studies have shown that the use of phages to control bacterial plant diseases is a promising option, because they are cheap to produce, self-destructible, and safe for the host organism and the biosphere, since they are a natural part of it [ 68 , 69 ]. An undeniable advantage of phages in comparison with other agents for the control of bacterial diseases is the possibility of their use to control synthetic biocide-resistant forms of bacteria [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…oryzae ( Xoo ), is one of the most serious diseases in rice production, which mainly occurs in tropical and temperate regions 1,2 . The occurrence of this disease leads to a significant reduction in rice yields, along with a decrease in rice quality 3,4 . The most effective and economical way to control BLB is breeding and cultivating rice cultivars that possess genetic resistance 5,6 .…”
Section: Introductionmentioning
confidence: 99%